Peranan K.H. Anwar Bin H. Kumpul dalam Pendirian dan Perkembangan Pondok Pesantren Nurul Islam Seri Bandung - Arenda Rosyada; Hudaidah Hudaidah (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
This study aims to determine the early history of the Nurul Islam Islamic Boarding School, and the role of K. H. Anwar in the establishment and development of the Nurul Islam Islamic Boarding School. Research conducted uses historical or historical research methods and uses a human approach. The research stages were source criticism, interpretation, heuristics, and historiography. The results show that K. H. Anwar played a very important role in the development of the Nurul Islamic Boarding School in Desa Seri Bandung. After establishing the Nurul Islamic Boarding School, he gave birth to several successors who have become religious scholars and teachers throughout South Sumatra and other regions. K. H. Anwar wrote a lot of books and used as study books for students. K. H. Anwar has created a pesantren with his hard work such as writing books, formulating curricula, disciplinary rules, traditions which are currently still partially implemented and also improving Islamic education in his home region until this pesantren is known in South Sumatra.